The use of social media for infrastructure developer company: study of a new revenue stream - G Aji Sentosa; Eri Dwi Wibawa; Ines Wahyuniati Rizaa; Annisa Dewanti Putri (Penerbit Universiti Kebangsaan Malaysia, 2023)
The culture of business construction, which currently focuses on winning new project tenders and revenue based on terms, is significantly affected when activity restrictions occur. What happened during the pandemic in 2019 noting that 25% of construction companies could not survive the pandemic. As a result, various innovations need to be deployed to save the business from bankruptcy, so that new revenue streams are needed outside of the ongoing business, one of which is the development of social media. Social media has an increasingly prominent role in impact interactions, and it has been proven that this sector does not experience a decline when almost all sectors are bad in the pandemic era. This research will examine how social media can have an impact on the construction industry, not only increasing participation and driving public opinion but can also be a new revenue stream for companies. This research will focus on companies engaged in toll road infrastructure developer in Indonesia. The case study was designed to combine both qualitative and quantitative methods. The results show that the use of social media in infrastructure development businesses that focus on corporate branding can be developed into a new revenue stream with a content focus, namely project progress, educational shows, and the use of technology impact the influence and awareness. Keywords: Construction; infrastructure developer company; revenue stream; social media Pembinaan; syarikat pemaju infrastruktur; aliran hasil; media sosial